ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN RISIKO - Ellen, Ellen; Siregar, Anitaria (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2023)
The purpose of this research is to analyze the factors that influence risk disclosure. The population used is the primary consumer industrial sector companies listed on the IDX in 2018-2020. The sample used is as many as 195 companies selected with predetermined criteria. The data was processed using SPSS 25. The data processing method was descriptive statistical analysis and multiple linear regression analysis. The results of this study indicate that profitability has a significant effect on risks disclosure. Meanwhile, the independent board of commissioners, the quality of external auditors, and competition do not have significant effect on the risks disclosure.